Economic and Ecological Externalities in Spatial Planning - Hołuj, Artur (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
Spatial planning, including space management, is a difficult task, especially in view of the limited resources available. Furthermore, the production of public and private goods generates external effects in the city space. Considering the complexity of this problem, a theoretical discussion on the issue of external effects (spillover) in space planning was undertaken (especially when residential areas are developed). The consideration were focused on the economic, but also on the natural and technological externalities accompanying the spatial economy